Modeling and Simulation of Grid Connected Hybrid Energy System and its Fault Analysis - Sujit Kumar Bhuyan; Prakash Kumar Hota; Bhagabata Panda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper represents a hybrid energy system (HES) consisting of photovoltaic (PV), Solid Oxide Fuel Cell (SOFC), electrolyzer system and a storage tank. In this proposed system a fuel cell controller is used where a PID controller is utilized to control the flow of hydrogen (H2) through the valve to the SOFC to fulfill the load requirement. In this model a supervisory controller is used to regulate the whole system according to load requirement. So, when PV power is more than load requirement, then PV power fulfill the required load demand as well as the extra power of PV is utilized to generate the hydrogen (H2) by the help of electrolyzer, further this hydrogen is used as a fuel of SOFC. Also in this proposed model different types of faults are considered and verified their effect on the load as well as in distribution network. The computer simulations are done for the purpose technology and verified its effectiveness. Hence the appropriate results are obtained.